Pyrolysis of polyurethane foam: optimized search for kinetic properties via simultaneous K-K method, genetic algorithm and elemental analysis - Li, Kaiyuan; Pau, Dennis Suwee; Zhang, Heping (Fire and materials, 2016)
Summary This study focuses on the determination of kinetic properties for non‐fire retardant (NFR) and fire retardant (FR) polyurethane foams. Based on the experimental thermogravimetric (TG) curves, this paper describes the application of an in‐depth mathematical analysis and genetic algorithm (GA) to produce the kinetic properties. A recent developed technique, K–K method, is used for calculating kinetic properties and determining the search regions of these properties for GA. Elemental analysis is also used to study the pyrolysis mechanism. Three decomposition models were investigated for comparison, and the results show that the decomposition model with three sub‐reactions achieves the closest representation with experimental results. In the model, two sub‐reactions capture the foam and melt decompositions, and another sub‐reaction with relatively lower activation energy captures the early onset of foam decomposition. The kinetic properties of melt decomposition are found similar because of the similarity of melt chemical formulas and decomposition of NFR and FR foams. The kinetic properties of foam decomposition between NFR and FR foams are different because of the mechanism of FR additives. Validation of the successive and parallel reaction schemes shows no noticeable difference between the two schemes in the modelling decomposition. Copyright © 2015 John Wiley & Sons, Ltd.